Impact of Sewage Water Irrigation on Soil and Radish (Raphanus sativus L.) with Respect to Heavy Metals in Tarlai, Islamabad - Zeeshan, M.; Shehzadi, S. (The Nucleus, 2019)
With increasing population and urbanization, the sewage water generated by domestic, industrial and commercial sources has increased. In the Urban areas, sewage water is used as a source of irrigation water as it contains organic and inorganic elements essential for plant growth. However, sewage water may also contain heavy metals which contaminate the soil and toxic for plants which is a potential health risk to consumers. For this purpose, a study was conducted at Tarlai farms, Islamabad, Pakistan in 2016 to observe the impact of sewage water on heavy metals (Pb, Cd, As) content in soil and its accumulation in radish. The sewage water, soil and radish samples were collected at 7, 14, 20, 40 and 60 days after sowing (DAS) from farmer’s field where use of sewage water for irrigation purpose is a regular practice for many years. The samples were analyzed using Atomic Absorption Spectrometry (AAS) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The physico- chemical analysis of experimental soil at 0-15 cm depth indicate that it is sandy clay loam in texture, alkaline in reaction, non-saline with 0.08% total nitrogen and 1.8% organic matter. The results show that the concentration of heavy metals in sewage water and soil are in safe limits. However, in radish, the concentrations of heavy metals (Pb and Cd) are above than the permissible levels set by the World Health Organization (WHO). The highest concentrations of Pb (1.0 mg kg-1) and Cd (0.65 mg kg-1) in radish are found at 7 DAS while maximum level of As (0.42 mg kg-1) is recorded at 40 DAS. The levels of heavy metals in radish plant is found in the order of Pb > Cd > As.